Coping strategies for handling stress and providing mental health in elite athletes: a systematic review - Nuetzel, Barbara (Frontiers in Sports and Active Living, 2023)
The combination of stressors unique to the athletic context plus the sensitive developmental phase that elite athletes go through during their peak performance may increase the athletes' vulnerability to mental health decrements. To emphasize the necessity to raise elite athletes' awareness of health risks, it seems to be essential to teach them coping skills to handle stress and to make affected athletes aware of how to recognize, evaluate, and articulate potential risks to their health. Objective This systematic review analyzes coping strategies used by elite athletes to deal with stress and the effect of these strategies on mental health to identify gaps that future research could prioritize.The current review analyzes studies containing quantitative, qualitative, and mixed data and results, all of them focusing on coping strategies to deal with stress and the effect of coping strategies on elite athletes' mental health. Literature search for this systematic review took place between August and October 2023 and included the use of 3 electronic databases: PubMed, PsychINFO, SPORTdiscus. Results There were initially 5.705 hits from 3 electronic databases, hand search and from a complementary search in Google Scholar. After the screening process and quality appraisal 30 studies were included. The analyzed study results point to a broad spectrum of coping categories, elite athletes make use of to deal with stressful situations. The results of this review underpin the necessity that especially young athletes being confronted with a wide range of stressors, need to be taught mental skills to cope with these stressors. In addition, teaching coaches and teammates about social support seemed to decrease elite athletes' stress reactions, such as anxiety or depressive symptoms.Coping in elite sporting settings is very complex and dynamic. There is evidence of coping being effective to buffer stress, but the interrelationships between stressor, appraisal of the stressor, application of a corresponding coping strategy and its effect especially in terms of mental health outcomes is still unclear because of lacking intervention-based study designs.